Surface mass balance and energy balance of the 79N Glacier (Nioghalvfjerdsfjorden, NE Greenland) modeled by linking COSIPY and Polar WRF - Blau, Manuel; Turton, Jenny; Sauter, Tobias; Mölg, Thomas (Journal of Glaciology, 2021)
To get a better overview of atmosphere-driven mass changes at the 79N Glacier (Nioghalvfjerdsfjorden Glacier), the largest outlet glacier of the northeast Greenland ice stream, the surface mass balance (SMB) is modeled by linking the COupled Snowpack and Ice surface energy and mass-balance model in PYthon (COSIPY) with the output of a regional atmospheric model (Polar WRF) for the years 2014-2018. After a manual model optimization, the model produces reliable results when compared to observations in the region and to values from the literature. High spatial resolution (1 km) simulations reveal strong interannual variability of the SMB. Stronger surface melting increased the ablation and runoff in years with high mass loss (2016 and 2017) whereas in other years (2015 and 2018) melting and refreezing inside the snowpack dominated the mass balance (MB). A cooler regional climate with higher snowfall-driven accumulation, higher albedo and reduced surface melt in the ablation period of 2018 resulted in a positive SMB in 2018, however, the annual total MB remained negative. The results suggest a promising new dataset for gaining more insights into mass-balance processes and their contribution to the acceleration of glacier retreat in northeast Greenland.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Glacier mass balance; glacier modeling; ice/atmosphere interactions; mass-balance reconstruction; surface mass budget

The Indian Ocean Dipole and its Impact on East African Short Rains in Two CMIP5 Historical Scenarios With and Without Anthropogenic Influence - Blau, Manuel; Ha, K. J. (Journal of Geophysical Research: Atmospheres, 2020)
The Indian Ocean dipole mode impacts the atmosphere and hydroclimate in areas surrounding the Indian Ocean. The Coupled Model Intercomparison Project 5 output was used in this study to reveal new aspects of the relationship between the dipole mode and East African “short rains” (occurring from September to November). Furthermore, the impact of human activity on the ocean-atmosphere system was investigated using two scenarios, one with and one without human forcings from 1960 to 1999. The Indian Ocean dipole and its teleconnection were simulated, and the impact of the dipole mode on the atmosphere displayed a similar pattern and strength under both scenarios. However, the dipole peak was slightly delayed from September to October under the scenario with anthropogenic warming. Further, increased moisture convergence over East Africa was found to enhance the local monsoon system during boreal autumn in the scenario considering anthropogenic forcing. More intense Walker and Hadley circulations were found with the presence of anthropogenic influences and the dipole mode had a significant impact on both. Positive Indian Ocean dipole events were found to temporarily weaken Walker circulation and strengthen Hadley circulation.
CRIS-Team Scopus Importer:2020-09-04
Keywords: CMIP5 models; East African precipitation; human impact detection; Indian Ocean dipole mode; short rains; tropical circulation